Conditional Generosity and Deservingness in Public Support for European Unemployment Risk Sharing. (14th December 2021) - Baute, Sharon; Nicoli, Francesco; Vandenbroucke, Frank
Abstract: Previous research into public support for welfare solidarity often refers to the importance of 'reciprocity', which means that generous social benefits are supported if they are matched by credible commitments to contribute by those who can. The current article adds to this body of literature by providing novel empirical evidence on the roles of generosity and conditionality in support for European unemployment insurance programmes. Drawing on a conjoint survey experiment in 13 European countries, we show that Europeans may be motivated by an ethos of reciprocity, since policy proposals that are both generous and conditional are the most popular among the general population. However, conditional generosity seems to have much more traction among those who consider the unemployed as undeserving, suggesting that EU‐level policies may succeed in overcoming the diffidence of welfare sceptics if reciprocity is ensured in the architecture of the policy design.